2019
DOI: 10.21037/jtd.2018.12.48
|View full text |Cite
|
Sign up to set email alerts
|

Molecular markers and prediction of response to immunotherapy in non-small cell lung cancer, an update

Abstract: Immunotherapy represents one of the most promising therapeutic approaches in lung cancer, however 50% of lung cancer patients will not respond to this treatment, while others will have transitory or durable responses. Because side effects may be life threatening and treatment costs remain very high, the identification of predictive markers is mandatory and actually extensively studied. Factors that determine response to immune checkpoint inhibitors (ICI) are numerous including tumor microenvironment, immune tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 61 publications
0
40
0
Order By: Relevance
“…In the present study, ORR according to RECIST1.1 was 20%, which is consistent with previous studies reporting an ORR of 15-26%. In numerous previous reports, molecular markers for prediction of response to nivolumab treatment were investigated, as the positive expression of PD-L1 and high tumor mutation burden were associated with significantly higher ORR than the others (5,6,25,26). The present univariate analysis showed that the number of bone metastases and bone response assessed by the MDA criteria were the risk factors for patients with PD.…”
Section: Discussionmentioning
confidence: 57%
“…In the present study, ORR according to RECIST1.1 was 20%, which is consistent with previous studies reporting an ORR of 15-26%. In numerous previous reports, molecular markers for prediction of response to nivolumab treatment were investigated, as the positive expression of PD-L1 and high tumor mutation burden were associated with significantly higher ORR than the others (5,6,25,26). The present univariate analysis showed that the number of bone metastases and bone response assessed by the MDA criteria were the risk factors for patients with PD.…”
Section: Discussionmentioning
confidence: 57%
“…3,48 Conversely, tumours with oncogene addiction such as non-small cell lung cancer with ALK fusion or EGFR mutation have been shown to have lower TMB and lower likelihood of response to ICI in lung cancer. 61,62 While these findings require validation across tumour types and contexts, they raise the question of whether tumours with a single gene driver -such as iCCA with FGFR2 fusions -may harbour fewer tumour-associated antigens and consequently have lower response rates to ICI. Future subanalyses of ICI studies in CCA, according to tumour mutational status, are needed to confirm whether certain genetically defined subgroups are more or less likely to respond to ICI.…”
Section: Tumour Geneticsmentioning
confidence: 99%
“…However, most of them focused on PD-L1 and TMB as biomarkers, went into detail on specifically selected pathways, e.g. the WNT signaling pathways, or summarized prognostic factors for both treatment success and for overcoming resistance to ICI [68][69][70]. Beside including the latest results for biomarkers from post hoc analyses of recently published Phase III trials, this review focuses on factors that are easily identified in daily clinical practice prior to initiating ICI based therapy.…”
Section: Introductionmentioning
confidence: 99%